2009
DOI: 10.5751/es-02734-140105
|View full text |Cite
|
Sign up to set email alerts
|

Reconnecting Social and Ecological Resilience in Salmon Ecosystems

Abstract: ABSTRACT. Fishery management programs designed to control Pacific salmon (Oncorhynchus spp.) for optimum production have failed to prevent widespread fish population decline and have caused greater uncertainty for salmon, their ecosystems, and the people who depend upon them. In this special feature introduction, we explore several key attributes of ecosystem resilience that have been overlooked by traditional salmon management approaches. The dynamics of salmon ecosystems involve social-ecological interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 43 publications
(87 reference statements)
0
63
0
Order By: Relevance
“…Furthermore, this stock-specific variation likely contributes to the overall resilience of salmon populations, allowing species to persist despite unpredictable environmental variation that may favor some strategies over others in given time periods (e.g., Thorpe 1999;Schindler et al 2010;Bottom et al 2011). Clearly, stock-specific traits are critical to successfully transitioning from one life stage to another, yet they are often overlooked when different stocks originate from a common river basin.…”
Section: Variation In Life History Traitsmentioning
confidence: 99%
“…Furthermore, this stock-specific variation likely contributes to the overall resilience of salmon populations, allowing species to persist despite unpredictable environmental variation that may favor some strategies over others in given time periods (e.g., Thorpe 1999;Schindler et al 2010;Bottom et al 2011). Clearly, stock-specific traits are critical to successfully transitioning from one life stage to another, yet they are often overlooked when different stocks originate from a common river basin.…”
Section: Variation In Life History Traitsmentioning
confidence: 99%
“…The emphasis on biophysical outcomes is understandable and, indeed, justifiable as biophysical systems are obviously fundamental to human well-being. There is also ample literature that acknowledges the validity of normative cultural valuation of landscapes, natural resources, and livelihood practices (Watson et al 2003, Xu et al 2005, Bottom et al 2009), as well as the "social limitations of adaptations" (Adger et al 2009). However, there is little that explores the relationships between empirical biophysical models and normative cultural models in ways that are robust, synergistic, and practical, although some movement is being made in that direction (Berkes and Jolly 2002, Stepp et al 2003, Jansen 2009, Meinke et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of the Kitlope Heritage Conservancy protected area has clearly fostered social resilience and human "response diversity" (concept discussed in Bottom et al 2009). For example, the Conservancy provides an important venue for the dissemination and maintenance of Haisla local and traditional ecological knowledge through cultural rediscovery field camps for children (Lertzman 2002) and local field-based college courses where Haisla and non-Haisla students are exposed to traditional and scientific ecological knowledge in an integrated framework.…”
Section: Merits and Limits Of Ecosystem Protectionmentioning
confidence: 99%
“…For example, Hilborn et al (2003) demonstrated that the sustained productivity of the Bristol Bay, Alaska sockeye stock complex through numerous climatic regime shifts was a result of a management strategy that preserved biocomplexity within the larger aggregate population by curtailing fisheries on less productive (precarious) stocks. In turn, diverse and abundant salmon populations drive ecosystem processes in ways that directly and indirectly benefit many other species (Gende et al 2002), and foster resilience in human communities (Bottom et al 2009). …”
Section: Resilience Of Kitlope Salmonmentioning
confidence: 99%